Development of an Attachable Endoscopic Nerve Stimulator for Intraoperative Neuromonitoring during Endoscopic or Robotic Thyroidectomy. (21st November 2017) - Sung, Eui‐Suk; Lee, Jin‐Choon; Kim, Seok Hyun; Shin, Sung‐Chan; Jung, Da‐Woon; Lee, Byung‐Joo
Abstract : We developed a simple attachable endoscopic nerve stimulator that can be connected to monopolar cauterization surgical instruments. This study on porcine models aimed to investigate the feasibility and efficacy of an attachable endoscopic nerve stimulator for intraoperative neuromonitoring (IONM) before application in humans. We evaluated the electromyography (EMG) amplitudes of 8 recurrent laryngeal nerves in 4 pigs with a conventional nerve probe and the attachable endoscopic nerve stimulator. The attachable endoscopic nerve stimulator was feasible and safe in all cases. There was no significant difference in the EMG amplitude of the recurrent laryngeal nerve among instruments ( P =. 429). The application of stimulating dissection with an attachable endoscopic nerve stimulator during endoscopic or robotic thyroidectomy with IONM is simple, convenient, and effective. It provides surgeons with real‐time feedback of the EMG response during intermittent IONM. We believe that this novel device could be an essential guide and functional navigator for most surgeons, especially for less experienced ones.